Elections in Kazakhstan: the transformation of the electoral process - Amirzhanova, A.M.; Zelenin В.В.; Askeeva Г.Б. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2022)
The article presents a comparative analysis of evolutionary features of the formation and development of representative bodies through the election institute, which is one of the important and topical issues in the context of the democratization of modern Kazakhstan. The main purpose of the scientific paper is a detailed analysis of elections in the formation of representative power in the Republic of Kazakhstan from the point of view of political science. This is due to the fact that the electoral process in the country develops in accordance with the democratic regime and undergoes legislative reforms, as well as related difficulties.The peculiarity of the article is the detailed analysis of the evolutionary development of the electoral process through such valid methods as comparative analysis and cross-temporal comparisons. The characteristics of the evolution of elections in the Republic of Kazakhstan are defined based on a careful examination. The election system and stages of the electoral process that influence political party ratings have been investigated. The structure of representative authority in Independent Kazakhstan has been studied, as well as the characteristics of electorate participation in elections, the proportion of women in the chamber of Mazhilis of the Parliament, the number of parties, and the average age of deputies.As a result of the study, scientific conclusions were made and hypotheses to improve the electoral system of the country were proposed.Thus, the analysis of the process of formation of Kazakhstan’s electoral system is important not only for the study of the electoral policy itself but also to assess the prospects for further democratization of the political system of Kazakhstan. It is the institution of elections that determines and directs the process of democratic construction and is the main condition for the development of the modern political system.